Longitudinal variability in lateral hydrologic connectivity shapes fish occurrence in temporary floodplain ponds - Couto, Thiago B. A.; Zuanon, Jansen; Olden, Julian D.; Ferraz, Gonçalo (Canadian Journal of Fisheries and Aquatic Sciences, 2018)
Dynamic flow regimes maintain critical connections between main channel and adjacent floodplain habitats that provide fish access to shelter, foraging, and spawning opportunities. Our study advances the understanding of these processes by exploring the importance of coupled longitudinal-lateral connectivity for determining species occurrence in headwater streams of the Amazon. Using a multispecies occupancy model, we revealed a clear pattern of species addition in the downstream direction in temporary floodplain ponds, associated with changes in the pool of potential colonists present in the channel and with increasing lateral hydrologic connectivity. Species that are more tolerant of stagnant waters and those able to disperse in shallow habitats (e.g., Anablepsoides micropus) occurred frequently in ponds along the entire longitudinal extent, whereas those species preferring lotic habitats were present only in the most downstream sites. We also observed increasing similarity of pond and channel communities with distance downstream. This study provides insights on the spatial structuring of tropical fish communities in response to flood-induced hydrologic connectivity and further highlights the vulnerability of floodplain fishes to modification in flooding regimes. © 2018, Canadian Science Publishing. All rights reserved.
Keywords: Channel; Connectivity; Ecological Modeling; Finfish; Floodplain; Headwater; Hydrological Regime; Longitudinal Gradient; Pond; Species Occurrence; Tolerance; Amazon River; Micropus; Pisces